Atypical Uptake of 18FDG in White Adipose Tissue During PET/CT in Children - M. M. Dunaikin; Ch. Kailash; E. D. Kireeva; N. L. Komarova; Yu. N. Likar (Вестник рентгенологии и радиологии, 2023)
Positron emission tomography combined with computed tomography (PET/CT) with 18F-fluoro-deoxyglucose (18F-FDG) plays an important role in the management of cancer patients and is mainly used for primary staging, evaluation of treatment response and detection of disease recurrence. Due to non-specific nature of 18F-FDG uptake, a radiologist must be familiar with both physiological and atypical distribution of radiopharmaceuticals. Inappropriate patient preparation for the study and/or taking certain drugs can lead to abnormal 18F-FDG distribution. Our clinical case demonstrates an atypical uptake of 18F-FDG in white adipose tissue in a child treated with glucocorticoids for a long time.